Efficacy of Cyclosporine in the Induction and Maintenance of Remission in a Systemic Lupus Erythematosus Patient Presenting with Macrophage-Activating Syndrome - Franchesca Cruz-Pérez; Salvador Vilá; Grissel Ríos; Luis M. Vilá (Case Reports in Rheumatology)
Macrophage-activating syndrome (MAS) is a rare condition characterized by dysfunctional macrophage activation leading to overproduction of cytokines and phagocytosis of erythrocytes, leukocytes, and platelets. MAS is associated with infectious diseases, malignancies, and autoimmune rheumatic disorders. Herein, we present a 22-year-old Hispanic woman with SLE who was hospitalized because of a three-week history of fever, fatigue, polyarthralgia, nausea, and abdominal pain. Initial laboratories showed severe pancytopenia with marked elevation of liver enzymes and ferritin levels. Bone marrow biopsy revealed macrophages with engulfed erythrocytes consistent with MAS. The patient was treated with high-dose corticosteroids, intravenous immunoglobulins, and cyclosporine 3 mg/kg/day. She had a remarkable clinical response to this therapy. She was continued on cyclosporine, and prednisone dose was gradually decreased to 7.5 mg daily without experiencing recurrent disease. She remained in full clinical remission for 12 months. Our case, together with other reports, suggests that combination therapy with corticosteroids, immunoglobulins, and cyclosporine appears to be effective for patients with SLE-associated MAS. Furthermore, cyclosporine seems to be a good drug for maintenance of remission.